The Protection of Consumer Rights against Illegal Online Loans - Nurdania, Esa; Suherman, Suherman (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This research is intended to examine the form of protection provided by the government for rights violations committed by illegal online loan companies. This research also intends to provide input for the government regarding its role in dealing with the problem of illegal online loans. This research uses normative juridical research methods. The problem approach in this research uses a statutory approach. The results of this study indicate that POJK Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending and Borrowing Services (LPMUBTI) and the Consumer Protection Law have not specifically regulated the legal rules related to illegal online loans. In addition, the government must immediately form a law that can provide a deterrent effect for illegal online loan companies.